O trabalho de mulheres assentadas: descortinando desigualdades - Faccin, Rodrigo Duarte (2016)
Thus, women's work becomes not recognized, unviable and sometimes without generating economic and social value. In the context of looking for recognition of the women as rural workers, this study aimed to analyze gender relations from the meanings expressed by farmers about the work. The initial step of the research took place from an existing connection with the Conquista da Liberdade Settlement in Piratini-RS. An important factor for choosing this Settlement as the universe of the research was the presence of two models of work organization: (1) individual, the lands are used individually by each family through agricultural production model of family farming and (2) collective, the families use a collective land production system through a cooperative. As the goal of obtaining detailed knowledge, we conducted a case study, which sought to reclaim the women's experiences and analyze their perception about the work through observation and oral report of eight farmers. It was possible to know the harsh reality that these women are inserted, having their work slighted while men occupy the positions of power and decision-making. The settlement studied is a space of multiple social relationships, in which community life is built from various aspects, either through interaction that work creates between families or even from some elements such as religiosity and parties in the community. All those spaces are architected from a deep division in gender social roles. The process of struggle for land owned an educational role for families, especially for women, with regard to the recognition of their role in agriculture. However, it is appropriate to point out that these women still do not recognize as work all the activities they perform, mainly those carried out in the domestic sphere, and perceive to be their husbands helpers in other activities, particularly those related to agricultural work. In this way, the representation of a man as the head of the family is constantly constructed and evidenced. It was possible to notice that both the experience of collective work as the model of individual work has contributed to sustain inequality between men and women, presenting from a naturalization of the division of labor. This division of labor prevents women's participation in leadership areas, establishing the men the power of decisions. In addition, it produces overload and devaluation of women's work. It is worth noting that the spaces for debate, reflection and training in the settlement are currently rare but it was a very stimulated practice by the movement and incorporated by the settlers in the past. Finally, it is also worth mentioning that women have shown us how experience unequal labor relations, creating dreams of egalitarian gender relations. Generally speaking, they brought to light the inequalities at the same time they showed: never fear!